Lagenorhynchus acutus - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
2. Adantic White-sided Dolphin Lagenorhynchus acutus French: Dauphin a flancs blancs / German: Atlantik-Weif 3seitendelfin / Spanish: Delfin de flancos blancos del Atlantico Other common names: Atlantic White-sided Porpoise, Jumper, Skunk Porpoise Taxonomy. Delphinus acutus Gray, 1828, type locality unknown. Later designated by J.E. Gray in 1846 as “North Sea, Faroe Isls (Denmark).” Taxonomy of Lagenorhynchus is currently in dispute. Recent molecular analyses have revealed that the genus is not monophyletic. L. acutus may actually belong to an isolated lineage within Delphinidae. The genus Leucopleurus has been suggested as an alternative placement for L. acutus. Monotypic. Distribution. Cold temperate to subarctic waters of the N Atlantic Ocean (including mouth of the Saint Lawrence River, Canada, but excluding the Baltic Sea), S to ¢.38° N in W Atlantic Ocean, and from S Svalbard to the Brittany coast, France, in the E Atlantic Ocean. Descriptive notes. Total length ¢.280 cm (males) and ¢.250 cm (females); weight c.235 kg (males) and c.182 kg (females). Neonates are 110-120 cm long and weigh c.25 kg. Like the White-beaked Dolphin (L. albirostris), the Atlantic White-sided Dolphin has robust body shape and short beak. Dorsal fin, positioned just posterior to halfway on back,is tall (more than 12% of total body length), falcate, and pointed. Flippers are broad, pointed at tips, and covered in tubercles along leading edges. Tailstock is also characteristically deep. The Atlantic White-sided Dolphin has a complicated color pattern. Dorsal surface, including upper jaw, top of head, dorsal fin, and flukes are a dark gray to black, but lower jaw, throat, lower anterior flanks, and belly up to urogenital area are white. Lateral body in between these dorsal and ventral areas and ventral tail posterior to urogenital area are typically medium-todark gray. Thin, dark bands stretch between dark edges of upper jaws to small, dark patches around eyes and from eyes down to anterior bases of flippers. There is a white streak ...